Participation in research projects - Christodoulou, Constantinos (My University, 2026)
Member of MEP Reasearch team in project NANOSONICS 2019-2022 of Cyprus Research Promotion Foundation. Principal Investigator: Dr G. Itskos (UCY), CUT/MEP Project Role (Partner), CUT/MEP (Scientific Coordinator) Prof S. Choulis, member of MEP Dr C. Christodoulou.